Oberhalb der Baumgrenze. - Mennekes, Friedhelm; Pagnes, Andrea; Pauly, Bettina (München : Popa-Verlag, 1990)
Böninger, Stephan ; Pfahler, Heinz ; Jetelova, Magdalena ; Reusse, Stephan ; Cragg, Tony (Anthony) ; Vaccari, Wainer ; Tornata, Ben ; Finlay, Ian Hamilton ; Bohnenberger, Stefan ; Dahn, Walter ; Hell, Eldo ; Schwenk, Martin ; Bohnenberger, Stefan ; Erdmann, Andreas ; Mlecko, Martin ; Trockel, Rosemarie ; Burkel, Ernst ; Boltanski, Christian ; Schult, Emil
Oberhalb der Baumgrenze, Schloss Gut-Granerhof, Peissenberg, 5. - 29. August 1990
Duits
kunstcatalogus